SKILLINGEN, BRODEREN OG TABLETTEN: Penge og sundhed i det østlige Uganda - Mogensen, Hanne O. (Tidsskriftet Antropologi, 2004)
Complaints about fees at the government health facilities in Uganda are incessant, and so are the more general statements about lack of money and problems of poverty. These complaints, however, cannot be reduced to questions of cost and the availability of resources. We also need to look at the kinds of exchanges money is made part of. Health has long been part of the economic sphere in Uganda, and people compensate healers and practitioners of different kinds for their services. The article explores why, then, people experience it as far more problematic to pay for treatment in the public health care system than to pay other health care providers. To answer this question requires a discussion of money, not as destructive to social relations, but as creative potential for relationships in all spheres of everyday life. In Uganda, as elsewhere, money can be used both to pay somebody and to give somebody something. Money is being made part of different modalities of exchange. In order to understand what takes place in various kinds of clinical interaction we need to look at the complex intersection of social relations, modalities of exchange, and the objects exchanged.